Biomarker Signatures of Quality for Engineering Nasal Chondrocyte-Derived Cartilage - Asnaghi, M. Adelaide; Power, Laura; Barbero, Andrea; Haug, Martin; Köppl, Ruth; Wendt, David; Martin, Ivan (Frontiers in Bioengineering and Biotechnology, 2020)
The definition of quality controls for cell therapy and engineered product manufacturing processes is critical for safe, effective, and standardized clinical implementation. Using the example context of cartilage grafts engineered from autologous nasal chondrocytes, currently used for articular cartilage repair in a phase II clinical trial, we outlined how gene expression patterns and generalized linear models can be introduced to define molecular signatures of identity, purity, and potency. We first verified that cells from the biopsied nasal cartilage can be contaminated by cells from a neighboring tissue, namely perichondrial cells, and discovered that they cannot deposit cartilaginous matrix. Differential analysis of gene expression enabled the definition of identity markers for the two cell populations, which were predictive of purity in mixed cultures. Specific patterns of expression of the same genes were significantly correlated with cell potency, defined as the capacity to generate tissues with histological and biochemical features of hyaline cartilage. The outlined approach can now be considered for implementation in a Good Manufacturing Practice setting, and offers a paradigm for other regenerative cellular therapies.